2005
DOI: 10.1021/jf048298q
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Ferric Complexes with 3-Hydroxyflavone (Flavonol), 5,7-Dihydroxyflavone (Chrysin), and 3‘,4‘-Dihydroxyflavone

Abstract: The acid dissociation and ferric stability constants for complexation by the flavonoids 3-hydroxyflavone (flavonol), 5,7-dihydroxyflavone (chrysin), and 3',4'-dihydroxyflavone in 50:50 (v/v) ethanol/water are determined by pH potentiometric and spectrophotometric titrations and the linear least-squares curve-fitting program Hyperquad. Over the entire range of pH and reagent concentrations spanning the titration experiments, the stoichiometry for iron-flavonoid complex formation was 1:1 for all three flavonoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 36 publications
5
59
0
3
Order By: Relevance
“…The 5-hydroxy-4-keto site is another possible iron binding site, but this study showed and other researchers confirmed that its importance is lower when compared to the previously mentioned sites [7]. In addition, the complex formed at this site is less stable and iron can be easily released at more acidic conditions (see Fig.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The 5-hydroxy-4-keto site is another possible iron binding site, but this study showed and other researchers confirmed that its importance is lower when compared to the previously mentioned sites [7]. In addition, the complex formed at this site is less stable and iron can be easily released at more acidic conditions (see Fig.…”
Section: Discussionmentioning
confidence: 55%
“…deferoxamine (Fig. 1B), is missing [5][6][7][8][9][10][11]. The published studies uniformly reported the three most common iron binding sites of flavonoids: 1) catecholic ring B, 2) 3-hydroxy-4-keto and 3) 5-hydroxy-4-keto conformation [6,8].…”
Section: Introductionmentioning
confidence: 93%
“…For the second equilibrium ( Fig. 2(b)), around a pH close to pK 2 the peak at 260 nm due to the dianionic forms of puerarin increases and shows a red shift [20]. In the studied range of pH values, it is evident that tow isosbestic points exist at the wavelength point where the spectra cross up (315 nm ( Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Taxifolin has no conjugation, due to the absence of C2-C3 double bond, hence 3-O has higher charge than 5-O. Some studies report that 3'-4' site is the first chelation site [35]. This may be due to different solvent conditions (acidic or basic).…”
Section: Spin Density and Their Reactivitymentioning
confidence: 99%